Characterization and ozone formation potential (OFP) of non-methane hydrocarbons under the condition of chemical loss in Guangzhou, China - FLORES RANGEL, ROSA MARIA (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
The conventional analytical studies to determine ozone formation potential (OFP) and potential sources currently ignore the destruction of non-methane hydrocarbons (NMHCs) during atmospheric transport, namely chemical loss. The chemical loss of NMHCs was estimated using photochemical age based on the online observation data of NMHCs from the Guangzhou Panyu Atmospheric Composition Station (GPACS) in the Pearl River Delta (PRD) during summer (June, July, and August) and autumn (September, October, and November) - two seasons favorable to the photochemical generation of ozone - of 2012. Subsequently, the composition characteristics, OFPs, and potential sources of the NMHCs were analyzed under the condition of atmospheric photochemical loss. The results showed that the initial mixing ratios of NMHCs (i.e., the mixing ratios after discharge from emission sources, before they experience any significant atmospheric chemical reaction), during summer (37.30 ppbv) and autumn (41.62 ppbv) were 6.90 ppbv and 5.98 ppbv higher than the observed, respectively. Four maximum incremental reactivity (MIR) scales were used to calculate the OFP for NMHCs seasonal losses. The obtained OFPs were 62.67 ppbv, 73.05 ppbv, 73.31 ppbv, and 68.51 ppbv in summer and 47.71 ppbv, 55.54 ppbv, 56.12 ppbv, and 52.68 ppbv in autumn as calculated by the respective MIR scales. Both the MIR and the propylene-equivalent mixing ratio reflect the reactivity of various NMHC species to a certain extent. Isoprene, toluene, and xylene were found key species for controlling ozone. Based on the source analysis of the initial mixing ratio of NMHCs, vehicle emissions and solvent consumption were the major sources in Guangzhou.
Keywords: NMHCs; Photochemical pollution; MIR; PMF; Megacity; VOLATILE ORGANIC-COMPOUNDS; PEARL RIVER DELTA; AEROSOL OPTICAL-PROPERTIES; SOURCE APPORTIONMENT; MIXING STATE; HONG-KONG; VOCS; EMISSIONS; RATIOS; SITE